Meta-analysis and randomized controlled studies: what clinicists should know to prevent regular and spontaneous miscarriages of unexplained genesis? - Paul Piette (Publishing House TRILIST, 2021)
The etiopathology of recurrent miscarriage is a combination of various factors, including chromosomal defects, genetic or structural abnormalities, endocrine abnormalities, infections, immune dysfunction, thrombophilia disorders, antiphospholipid syndrome, and unexplained causes. It has long been known that progesterone is needed to maintain pregnancy and its physiological development. Insufficient progesterone secretion and its low level in the blood serum in early pregnancy is associated with the threat of miscarriage and loss of pregnancy at a later stage - up to 16 weeks of gestation. The effectiveness of the vaginal micronized progesterone (VMP) at a dose of 400 mg twice a day in the first trimester of pregnancy was evaluated in two recent large high-quality multicenter placebo-controlled studies, one of which included pregnant women with recurrent miscarriages of unexplained origin (PROMISE Trial), and the other study included women with early pregnancy loss (PRISM Trial). A key finding, pioneered in the PROMISE study and later confirmed in the PRISM study, was that VMP treatment associated with an increase in live births in line with the number of previous miscarriages. It has been shown that there is no evidence regarding safety concerns with natural micronized progesterone. Treatment with an VMP should be recommended for women with bleeding in early pregnancy and a history of one or more miscarriages. The recommended treatment regimen is 400 mg 2 times a day (800 mg/day) intravaginal, starting from the moment bleeding is detected up to 16 weeks of pregnancy. In the future, there remains uncertainty effectiveness and safety of alternative progestogens (dydrogesterone) for the treatment of women at high risk of threatened abortion and recurrent miscarriage. It is important that dydrogesterone is a synthetic progestin, its structure is significantly different from natural progesterone, and therefore it is necessary to unequivocally prove the short- and long-term safety of this drug before considering its use in clinical practice.